Спорт жамоаларида психологик хизмат кўрсатишнинг ижтимоий-психологик хусусиятлари - Арзымбетов, Т.Т (SCIENCE and SOCIETY, 2023)
The problem of providing psychological services is considered in a certain sense as one of the leading areas of scien-
Keywords: man; psyche; sports teams; psychological service; psychodiagnostics; correction; activity; method; sports activity; im- provement